CircRNA_0075723 protects against pneumonia-induced sepsis through inhibiting macrophage pyroptosis by sponging miR-155-5p and regulating SHIP1 expression - Yang, Dianyin; Zhao, Dongyang; Ji, Jinlu; Wang, Chunxue; Liu, Na; Bao, Xiaowei; Liu, Xiandong; Jiang, Sen; Zhang, Qianqian; Tang, Lunxian (Frontiers in Immunology, 2023)
Circular RNAs (circRNAs) have been linked to regulate macrophage polarization and subsequent inflammation in sepsis. However, the underlying mechanism and the function of circRNAs in macrophage pyroptosis in pneumonia-induced sepsis are still unknown. In this investigation, we found circ_0075723, a novel circRNA that was significantly downregulated in pneumonia-induced sepsis patients compared to pneumonia patients without sepsis and healthy individuals. Meanwhile, pneumonia-induced sepsis patients exhibited activation of NLRP3 inflammasome and production of the pyroptosis-associated pro-inflammatory cytokines IL-1β and IL-18. circ_0075723 inhibited macrophage pyroptosis via sponging miR-155-5p which promoted SHIP1 expression directly. MiRanda and TargetScan were utilized to identify miR-155-5p binding locations within circ_0075723, and the target connection was verified using dual luciferase assay and RNA pull-down assay. circ_0075723 negatively regulated miR-155-5p expression, and miR-155-5p mimics partially reduced protective impact of circ_0075723 on macrophages pyroptosis. SHIP1 was recognized as a miR-155-5p target gene and circ_0075723 promote SHIP1 expression, while miR-155-5p mimics could effectively suppress SHIP1 upregulation induced by circ_0075723 overexpression. Besides, we found that circ_0075723 in macrophages promoted VE-cadherin expression in endothelial cells through inhibiting the release of NLRP3 inflammasome-related cytokines, IL-1β and IL-18, and subsequently altered endothelial permeability. Collectively, our findings propose a unique approach wherein circ_0075723 suppresses macrophage pyroptosis and inflammation in pneumonia-induced sepsis via sponging with miR-155-5p and promoting SHIP1 expression. These findings indicate that circRNAs could be used as possible potential diagnostic and therapeutic targets for pneumonia-induced sepsis.